Fungsi Actuating Dalam Layanan Perpustakaan di SMA Islam Terpadu Kota Palembang - Adek Purnama; Kms Badaruddin; Febriyanti Febriyanti (Studia Manageria, 2020)
This research is a research on the actuating function in library services which will discuss how the actuating function in library services, how library services are in SMAIT Kota Palembang as well as inhibiting and supporting factors for library services at SMAIT Kota Palembang. The research method used in this study uses a qualitative type and a phenomenological approach. The results of this study are 1)the actuating function in library services at SMAIT is an effort made by the principal to motivate librarians to be able to provide library services properly, the efforts that the head does are good leadership skills, effective communication and motivation to librarians. , 2) librarian library services use an open and mixed service system and provide several types of services, namely circulation services, reference services, literacy services, reading room services, and library education services which arecarried out once a year. The inhibiting factors for library services include the location and area of the library building, the time that visitors have to visit the library, the lack of attention from the government regarding the library. While the supporting factors for library services include adequate library room facilities, library budget funds, professional human resources who have a background in library education and communication science, support from school principals, the variety of library materials available at SMAIT Palembang City and reading corner programs and library free